2018
DOI: 10.1038/s41598-018-27284-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Porphyromonas gingivalis outer membrane vesicles in oral mucosal transmission of HIV

Abstract: The association between mucosal microbiota and HIV-1 infection has garnered great attention in the field of HIV-1 research. Previously, we reported a receptor-independent HIV-1 entry into epithelial cells mediated by a Gram-negative invasive bacterium, Porphyromonas gingivalis. Here, we present evidence showing that P. gingivalis outer membrane vesicles (OMVs) promote mucosal transmission of HIV-1. We demonstrated, using the Dynabeads technology, a specific interaction between HIV-1 and P. gingivalis OMVs whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In contrast to the defensive role of bacterial EVs described above, they may also facilitate the infection of oral mucosa with other pathogens, such as HIV-1. Dong and colleagues have reported a novel mechanism of HIV-1 entry into nonpermissive cells, in which EVs of P. gingivalis, an invasive oral bacterium, interact specifically with HIV-1 and promote a CD4-independent HIV-1 entry into epithelial cells [83].…”
Section: Oral Microbiota-derived Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the defensive role of bacterial EVs described above, they may also facilitate the infection of oral mucosa with other pathogens, such as HIV-1. Dong and colleagues have reported a novel mechanism of HIV-1 entry into nonpermissive cells, in which EVs of P. gingivalis, an invasive oral bacterium, interact specifically with HIV-1 and promote a CD4-independent HIV-1 entry into epithelial cells [83].…”
Section: Oral Microbiota-derived Evsmentioning
confidence: 99%
“…Dong and colleagues have reported a novel mechanism of HIV-1 entry into nonpermissive cells, in which EVs of P . gingivalis , an invasive oral bacterium, interact specifically with HIV-1 and promote a CD4-independent HIV-1 entry into epithelial cells [ 83 ].…”
Section: Bacterial Evs and Interaction With Human Hostsmentioning
confidence: 99%
“…In other cases, they can constitute the secretion pathway of enzymes involved in the degradation of complex substrates, as it has been shown for the degradation of cellulose by Bacteroides in the rumen (Forsberg et al, 1981). Recently, EVs secreted by Porphyromonas gingivalis were shown to promote HIV-1 transmission through oral mucosa (Dong et al, 2018). To date, the accumulation of data concerning EVs suggests that they are widespread in nature: they have been observed in domestic biofilms, in freshwater as well as in the ocean (Schooling and Beveridge, 2006;Biller et al, 2014).…”
Section: Extracellular Vesicles Secretion: a Widespread Phenomenon Wimentioning
confidence: 99%
“…P. gingivalis OMVs promote mucosal transmission of HIV-1. Dynabeads technology showed that a specific interaction between HIV-1 and P. gingivalis OMVs supports viral entry into oral epithelial cells [ 70 ]. Subsequently, HIV-1 was reverse-transcribed and viral DNA was integrated into the genome of these cells.…”
Section: Supporting Other Microorganismsmentioning
confidence: 99%
“…Recent studies using genetic, proteomic, and morphological tools have demonstrated that P. gingivalis OMVs include a variety of virulence factors provided by parental cells [ 70 ]. As described above, P. gingivalis OMVs possess various components of outer membrane constituents, including LPS, muramic acid, a capsule, fimbriae, and gingipains [ 41 , 42 ].…”
Section: Contents Of P Gingivalis Omvs and Movement In The Host Bodymentioning
confidence: 99%